Basic values predict unethical behavior in sport: the case of athletes' doping likelihood. Issue 1 (2nd January 2022) - Ring, Christopher; Kavussanu, Maria; Gürpınar, Bahri; Whitehead, Jean; Mortimer, Hannah
ABSTRACT: Although basic values have been linked with unethical attitudes and behavior in non-sport contexts, their association with doping in sport has yet to be established. We examined the relationships between basic values and doping likelihood. College athletes ( N = 233, 61% females) rated the importance of basic values using the Portrait Values Questionnaire Revised and indicated their likelihood of doping in a hypothetical scenario. In terms of basic value dimensions, self-enhancement values were positively related to doping likelihood, openness to change values were unrelated to doping likelihood, and self-transcendence and conservation values were negatively related to doping likelihood. In terms of the values categories, the values-doping relationship was best characterized by an unethicality pattern of coefficients. In conclusion, the current evidence extends the values-unethicality relationship to the context of sport and confirms that doping resembles other forms of unethical behavior.